A multicenter phase II study of Q3 week or weekly paclitaxel in combination with bevacizumab for the treatment of metastatic or unresectable angiosarcoma. (20th April 2018) - Bui, Nam; Kamat, Nikhil; Ravi, Vinod; Chawla, Sant; Lohman, Marti; Ganjoo, Kristen N
Paclitaxel (P) and bevacizumab (B) are agents that provide clinical benefit in advanced angiosarcoma (AS). The objective of this study was to assess the efficacy and safety of P-B in two different scheduled regimens. Patients were to receive P 200mg/m2 IV with B 15mg/kg IV every 21 days (Regimen A) or P 90mg/m2 IV weekly D1, 8, 15 with B 15mg/kg IV D1 of a 28 day cycle (Regimen B) x6 cycles. Maintenance B followed at a dose of 15 mg/kg intravenously once every 21 days. The primary end point was 4 month non-progression rate (NPR). A total of 16 patients were enrolled. 4 month NPR was 62.5% with median overall survival 16 months and median progression free survival 5.06 months. 11 patients made it to cycle 3 and were evaluable for response with 1 CR (9%), 4 PR (36%), 2 SD (18%), and 6 PD (36%). There were ten grade 3 toxicities and four grade 4 toxicities. The breakdown between the two regimens revealed comparable efficacy and safety. Paclitaxel and Bevacizumab is an active regimen in angiosarcoma. Q3 week and weekly paclitaxel appear similar in efficacy and safety.